Operating time prediction algorithm for synchronous switching on HVCB based on cloud theory - Jinlong Dong; Guogang Zhang; Yingsan Geng; Jianhua Wang (TENCON ... IEEE Region Ten Conference, 2013)
Precise prediction of operating time is one of the key factors for synchronous switching to minimize the control error. In this paper an operating time prediction algorithm is proposed based on cloud model, which shows a good applicability to synchronous switching technology on HVCB equipped with hydraulic operating mechanism. The algorithm uses cloud model to build up single-condition multiple-rule illation generators with which the uncertainty prediction is realized. The prediction model is tested for the closing operation with the experimental system. The test results show that the prediction error can satisfy the engineering requirements.